Quasiperiodic Oscillations in GRB 210514A: a Case of a Newborn Supramassive Precessing Magnetar Collapsing into a Black Hole? - Zou, Le; Cheng, Ji-Gui (The Astrophysical journal, 2024)
Magnetar is proposed as one of the possible central engines for a gamma-ray burst (GRB). Recent studies show that if a magnetar has a rotational axis misaligned from the magnetic one, a periodic lightcurve pattern is expected with a period of seconds to minutes. Inspired by this unique feature, in this paper, we search for the quasiperiodic oscillation (QPO) signals in the Swift observations of GRBs. Using the Lomb–Scargle periodogram and the weighted wavelet Z-transform algorithms, we find that the Swift Burst Alert Telescope data of GRB 210514A has a QPO signal with a period ∼11 s. The estimated confidence level of the signal is over 3 σ . The global lightcurve of this GRB exhibits a double-plateau structure with a sharp decay segment between plateaus. The lightcurve feature resembles those of GRBs that were reported to have internal plateaus. We explain the observations of GRB 210514A with a supramassive magnetar (SMM) model, where the QPO signal in the first plateau is produced via the dipole radiation of the SMM experiencing a precession motion, the sharp decay is due to the collapse of the SMM into a black hole (BH), and the second plateau could be produced via the fallback accretion of the newborn BH. We fit the precession model to the observations using the Bayesian statistic and the best-fit magnetar parameters are discussed. Alternative models concerning a BH central engine may also provide reasonable explanations for this burst, only in this case the QPO signal could merely be a coincidence.